The Impact of Peer Verbal Aggression on Automatic Negative Thoughts in Adolescent Bullying Victims - Yunita, Rizka; Widya Addiarto (Journal Of Nursing Practice, 2026)
Background: Adolescence is a crucial period for psychosocial development, with peer acceptance playing a central role. Peer verbal aggression, manifested through threats, offensive language, and insults, can act as a stressor for adolescents. These experiences may shape dysfunctional cognitive schemas. Recurrent and persistent negative thoughts can impact long term psychological development. Purpose: This study aims to analyze the relationship between peer verbal aggression and automatic negative thoughts in adolescent victims of bullying. Methods: This study employed a quantitative design with a cross-sectional approach. The sample consisted of 92 adolescents who were victims of bullying, selected through purposive sampling. Data were collected using a verbal victimization questionnaire adapted from an indicator of the Multidimensional Peer Victimization Scale (MPVS) and the Children’s Automatic Thoughts Scale (CATS). Data analysis was performed using the Spearman rank correlation test. Results: Most respondents were adolescents aged 15-17 years (91.3%), with 42.4% experiencing bullying for more than six months. Bivariate analysis revealed a significant correlation between peer verbal violence and automatic negative thoughts (p=0.001), encompassing physical threat (r=0.524), social threat (r=0.788), personal failure (r=0.703), and hostility (r=0.500). This suggests that higher exposure to peer verbal aggression is associated with a higher prevalence of automatic negative thoughts in bullying victims, which can disrupt their cognitive processes. Conclusion: Peer verbal aggression is a strong predictor of automatic negative thoughts in adolescent victims of bullying. The implications of this study underscore the need for psychological interventions, such as cognitive restructuring therapies, to reduce automatic negative thoughts.